Analisis Normatif Peran Otoritas Jasa Keuangan Dalam Mengelola Risiko Investasi Bodong Di Tinjau Dari Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan - Husnaini, Husnaini (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The role of the Financial Services Authority in monitoring and preventing illegal investment has benefited investment in Indonesia, as demonstrated by the establishment of the Investment Warning Treaty and various other preventive and repressive measures. However, this does not mean that the role of the Financial Services Authority is fully successful, as there are still illegal investment firms or illegal investment activities that succeed in escaping supervision. The activities of the Financial Services Authority have not been fully implemented in society. The Financial Services Authority is still making little effort to spread information to the public through socialization. In addition, the sanctions imposed on illegal investors are very mild, so they do not have a negative effect on them. The Financial Services Authority also forms a warning guard for investments to monitor investments, especially those that are obscure, such as illegal investments.